Forest restoration enhances plant diversity and carbon stock in the sub-tropical forests of western Himalaya - Bhawana Dangwal; Suresh K. Rana; Vikram S. Negi; Indra D. Bhatt (Trees, Forests and People, 2022)
In the present study we compared the community composition, structure, regeneration status and carbon stock of a human managed arboretum (restoration site) during three decades with a natural forest in western Himalaya. Results reveal that ecological restoration activities in the arboretum enhanced the species richness of woody plants by 66.4% with a total of 125 species as compared to 42 species in natural forest. Similarly, above ground carbon stock in the arboretum was ∼38% higher (49.5 Mg/ha) as compared to the natural forest (30.8 Mg/ha). Plantation success in the arboretum was ∼52% with a higher survival rate for temperate and Himalayan native species. Tree density in the arboretum was 322.6/ha with 50% higher density of small girth trees (<50 cm gbh) as compared to the natural forest with a tree density of 184/ha. Similarly, basal area was 41.5% higher in the arboretum (23.8 m2/ha) as compared to the natural forest (13.9 m2/ha). In case of the ground vegetation layer, shrubs, saplings and seedlings show a density of 23.5, 12.2 and 7.6 individuals/25 m2 in the arboretum as compared to 10.1, 3.0 and 4.1 individuals/25 m2 in the natural forest. Hence, our results indicate that the ecological restoration in the sub-tropical forests of the western Himalaya contribute 1.36% annual increment of above ground carbon stock in addition to improvement of the community composition, structure and regeneration in the forest. Therefore, similar institutional restoration projects have ample potential for reducing carbon emissions to mitigate the climate change impact. Such projects will aid in the implementation of the national commitment for REDD+ goals in addition to biodiversity conservation in the Himalaya.